Abbreviating the Early Start Denver Model for community-based family-centered care - Vismara, Laurie A.; Nyugen, Lucy; McCormick, Carolyn E. B. (Frontiers in Psychology, 2023)
Parent-mediated approached have gained traction, with mounting evidence of efficacy, but a research-to-gap practice exists, and community effectiveness remains to be firmly established. We report outcomes from in-person and virtual coaching of an abbreviated parent-mediated toddler intervention delivered through a research-community partnership, using a community-partnered participatory framework. Data from 10 parent-child dyads receiving a five-day workshop and six follow-up sessions of ESDM parent coaching showed improved parent fidelity and child gains on proximal measures of social communication. Facilitators and barriers to supporting parent learning and behavior change via interactive strategies are discussed. Community delivery of an evidence-based parent-mediated interventions for toddlers on the autism spectrum is feasible and promising. Giving resource efficiencies associated with parent-mediated approaches, particularly when delivered through government-funded programs, findings bolster current efforts to promote earlier and more widespread community access to necessary interventions.